EFFECTIVENESS OF TRIETHANOLAMINE ON GRINDABILITY AND PROPERTIES OF PORTLAND CEMENT IN LABORATORY BALL AND VIBRATING DISK MILLS - Ali Allahverdi; Zeinab Babasafari (Ceramics-Silikáty, 2014)

(untitled)
The aim of the present research work is to evaluate the effectiveness of one of the industrially most popular grinding aids (triethanolamine, TEA) on grindability, set and strength behavior of Portland cement in laboratory ball and vibrating disk mills when added at the same amount of 0.06 % by the weight of the cement. The results show that TEA is more effective in ball mill than in vibrating disk mill. It increases the Blaine specific surface area of the mixtures of 95 % clinker and 5 % gypsum by 16 and 7.6 % in ball and vibrating disk mills, respectively, compared to the blank test. The cement samples produced from the two mills were then tested for their initial and final setting times, spread diameter as a consistency measure and compressive strengths after 3, 7 and 28 days of curing. In both mills, addition of TEA increases both initial and final setting times and decreases compressive strengths at 3-, 7- and 28-day curing ages. The effects, however, are more significant in ball mill compared to vibrating disk mill.